State of the Evidence: A Systematic Review of Approaches to Reduce Gender-Based Violence and Support the Empowerment of Adolescent Girls in Humanitarian Settings. (July 2019) - Noble, Eva; Ward, Leora; French, Shelby; Falb, Kathryn
Adolescent girls are at an increased risk of sexual violence, abuse, exploitation, and forced or early marriage across humanitarian contexts. In the past few years, prominent initiatives, organizations, and working groups have started to highlight the targeted needs and issues facing adolescent girls and have developed programmatic responses such as safe spaces for adolescent girls to protect and empower girls and reduce their vulnerabilities to violence or exploitation. A systematic review of academic and grey literature was conducted in September 2015 to examine the evidence base for programming that seeks to reduce violence against adolescent girls in humanitarian contexts. The authors used a Boolean search procedure to find and review 5830 records from academic journal databases, resource-hosting websites and relevant organizational websites. The inclusion criteria left us with three adolescent girl program evaluations from humanitarian settings to examine, all of which were pre/post-test evaluations that looked at changes in indicators such as social assets, self-esteem, decision making, livelihood skills and financial assets, gender norms, and feelings of safety. While these three evaluations showed promising results, overall, this systematic review demonstrates a significant gap in currently available rigorous research. Evidence is urgently needed to guide programming decisions to ensure that the emerging programs provide the level and depth of protection that adolescent girls need in humanitarian settings.